Insufficient ventilation as a cause of impaired pulmonary gas exchange during submaximal exercise - Holmberg, H. C.; Calbet, J. A. L. (Respiratory Physiology & Neurobiology, 2007)
Pulmonary ventilation and gas exchange were determined during prolonged skiing (76% of ; cardiac output = 26-27 L min-1) using diagonal technique (DIA) for 40 min followed by 10 min of double poling (DPOL) and 10 min of leg skiing (LEG). Exercise caused 2-5% reduction of arterial oxygen saturation (SaO2). For a given cardiac output and , DPOL presented higher , lower PaCO2 and a more efficient pulmonary gas exchange, revealed by higher PAO2 and PaO2 and lower A-aDO2. The A-aDO2 widened 2 mmHg L-1 of cardiac output increase. However, for a given cardiac output and , exercise mode had an important influence on pulmonary ventilation and gas exchange. Highly trained cross-country skiers` present about 2 units reduction in SaO2 from resting values during submaximal exercise at 76% of . Half of the reduction in saturation is accounted for by the rightward-shift of the oxygen dissociation curve of the haemoglobin. The exercise duration has almost no repercussion on pulmonary gas exchange in these athletes, with the small effect on SaO2 associated to the increase in body core temperature.